New Isocoumarin and Pyrone Derivatives from the Chinese Mangrove Plant Rhizophora mangle-Associated Fungus Phomopsis sp. DHS-11 - Zhikai Guo; Biting Chen; Dandan Chen; Xiaoling Deng; Jingzhe Yuan; Shiqing Zhang; Zijun Xiong; Jing Xu (Molecules, 2023)
Mangrove-associated fungi are important sources for the discovery of new bioactive natural products. Three new isocoumarins (1–3) and one new pyrone derivative (4) were isolated from the ethyl acetate extract of the fermentation broth of the mangrove endophytic fungus Phomopsis sp. DHS-11. Nuclear magnetic resonance (NMR) spectroscopy (one-dimensional and two-dimensional) and mass spectrometry were used to determine the structures of these new compounds. The absolute configurations for the new isocoumarins 1–3 were determined by comparing their experimental and calculated electronic circular dichroism (ECD) spectra, while the configuration for the new pyrone-derivative 4 was tentatively solved by comparison of its 13C NMR data with reported data. In the biological activity test, compounds 1 and 3 showed cytotoxic activity against HeLa cells with IC50 values of 11.49 ± 1.64 µM and 8.70 ± 0.94 µM, respectively. The initial structure and activity relationship (SAR) analysis revealed that the length of the side chain at C-3 for isocoumarin-type compounds 1–3 could affect the cytotoxicity against HeLa cells. Compound 4 exhibited cytotoxic activities against human hepatoma cells HepG2 with an IC50 value of 34.10 ± 2.92 µM. All compounds have no immunosuppressive activity.